2005-2009 Quadrennium - a nationally coordinated approach to high performance (Ausport, 2003)
Full time has just been blown on the 2005.2009 Quadrennium, a forum to clarify sports high performance plans for the next cycle. The result? Institutes and academies of sport, the Australian Paralympic Committee, Australian Commonwealth Games Association and the Australian Olympic Committee will return to the Australian Institute of Sport (AIS) in February to confirm an agreed position on an overall nationally coordinated approach to high performance. Over the eight days of the November forum, national sporting organisations made presentations to representatives of the National Elite Sports Council, Australian Sports Commission (ASC), Australian Olympic Committee, Australian Paralympic Committee and Australian Commonwealth Games Association. ASC Manager of Sport Innovation and Best Practice, Phil Borgeaud, says the implementation of a nationally coordinated approach to the planning of high performance sport for the quadrennium will provide benefits for national sporting organisations and their program partners in the ASC, AIS and institute/academy network. The main benefits are enhanced athlete and program support which we believe will lead to improved athlete performance in targeted sports, and more efficient use of available resources, Mr Borgeaud said. With the forum now over, representatives of the ASC and AIS, and state institutes and academies will now consider submissions from national sporting organisations in detail, including changes in funding priorities. The representatives will look favourably on those sports that can demonstrate innovative thinking and provide increased efficiencies in their respective high performance programs, Mr Borgeaud said. The primary aim of the February 2004 meeting will be to confirm an agreed nationally coordinated approach to the delivery of the high performance plans of the targeted sports. The February meeting would also allow for further discussion with national sporting organisations where necessary in relation to any adjustments to high performance plans that may have arisen from discussion at the forum. The Quadrennium is a joint effort between the National Elite Sports Council and the ASC. Those sports that have been identified are the ones with the best chance of success at the 2006 Commonwealth Games, 2006 Winter Olympics and Paralympics, 2008 Olympics and Paralympics and other relevant international benchmark events, such as various world championships. Borgeaud cannot stress enough the importance of a coordinated approach to high performance sport. We want to coordinate the efforts of nine separately funded institutes and the major funding agencies so that the resources of the national elite sports system are used in such a way as to maximise our international success, he said.